Application of Socio-Drama Learning Methods In History Courses around Indonesian Independence Day Event to Raise Readability and Achievement Student in SMA Negeri 1 Surakarta in particular XI IPA Class - Winahyu Adha (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2017)
This study aimed to test the accuracy of Socio-Drama Methods in its effort to raisereadability and achievement student in SMA Negeri 1 Surakarta, especially aroundIndonesian Independence day event. So, writers try to apply this examination oflearning method directly involved in classroom. The research application carried outby using quantitative research methods, especially in Classroom Action Research.Researcher will examine Socio-Drama methods in history courses, especially aroundIndonesian Independence day event as a dependent variable, and aimed to raisereadability and achievement student in SMA Negeri 1 Surakarta in particular XI IPAclass as independent variable. In this study, researcher can solve the problem about thestudent saturation in learn history in SMA Negeri 1 Surakarta in particular XI IPAclass among the subject dominated by science, carried out using fun methods, sostudent can understand well. Beside that, student will not feel strange about thislearning method that will be applied, next, student can apply confidently. Therefore,teaching and learning process in classroom will feel harmony and interesting, eitherstudent as a learning object or teacher as a learning facilitator.Keyword: Socio-Drama, learning interest, and learning achievement.